Free vascularized fibular flap for clavicle reconstruction: A systematic review with a new case. (January 2023) - Wu, Y. H. Andrew; Riverol, Otoniel; Lee, K. X. Alvin; Chang, Kai-Hua; Harnke, Ben; Liao, Li-Ying; Chen, Hung-Chi
Summary: Background/objectives: Due to the rarity of the need for claviculectomy and the subsequent clavicle reconstruction, currently there is no consensus on the reconstructive approach for the clavicle. The clavicle is an essential bony structure that is necessary for optimal upper limb anatomical and physiological functionalities. Objective: This study analyzes the reconstructive approach, vascular anastomosis, complications, and long-term outcome of clavicle reconstruction using a free vascularized fibular flap through a systematic review of the literature and a case report from our institution. Methods: A comprehensive literature search was executed in the Ovid MEDLINE, Embase, and Google Scholar databases. The search strategy was designed to capture the concept of cases that underwent clavicle reconstruction after necessary claviculectomy with sufficient clinical information for detailed analysis. Using the final included articles, we analyzed and summarized the outcomes associated with clavicle reconstruction using free fibular osteocutaneous flap. Results: A review of 179 articles yielded 11 publications with 26 cases that had detailed clinical information. We presented an additional case from our institution database. The systematic review of 27 cases revealed that clavicle nonunion due to various causes accounted for 73.08% of the cases for claviculectomy and the eventual reconstruction with a free fibular flap. The mean follow-up period in this study is 29.54 months with the range of 3 to 120 months. A total of 92.31% of the cases showed evidence of complete osseous consolidation. Conclusion: When claviculectomy is necessary, a free fibular flap can be utilized for the subsequent clavicle reconstruction to provide optimal anatomical and physiological functionality of the clavicle.